2008
DOI: 10.1007/s12016-007-8055-9
|View full text |Cite
|
Sign up to set email alerts
|

Updating on the Pathogenic Mechanisms 5 of the Antiphospholipid Antibodies-Associated Pregnancy Loss

Abstract: Anti-phospholipid antibodies (aPL) are risk factor for recurrent pregnancy loss and obstetrical complications. The mechanisms of aPL-mediated pregnancy failure are still a matter of research. Although aPL are associated with thrombosis, thrombotic events cannot explain all the miscarriages. There is evidence for a direct in vitro aPL effect on the trophoblast as shown by their binding; reduction of proliferation, human chorionic gonadotrophin release, in vitro invasiveness, adhesion molecule expression; and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 48 publications
2
22
0
2
Order By: Relevance
“…While, secondary infertility is difficulty conceiving after already having conceived. In spite of the bulk knowledge about APA, the concept of autoimmune basis of infertility is still controversial, particularly regarding the presence of ACL [10] [11] [18]. In the present study, the significantly higher ACL IgM positivity rate in women with primary infertility was consistent with that reported by other workers [12] [14].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While, secondary infertility is difficulty conceiving after already having conceived. In spite of the bulk knowledge about APA, the concept of autoimmune basis of infertility is still controversial, particularly regarding the presence of ACL [10] [11] [18]. In the present study, the significantly higher ACL IgM positivity rate in women with primary infertility was consistent with that reported by other workers [12] [14].…”
Section: Discussionsupporting
confidence: 90%
“…The concept of autoimmune basis of infertility is still controversial, particularly regarding the presence of ACL [10] [11]. It has been found that in fertile women, ACL was below the negative cut-off value, while women with unexplained infertility were positive in 23.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy complications in APS (recurrent unexplained abortions, spontaneous fetal loss, preeclampsia [PE], and premature birth) have been attributed to placental thrombosis and infarcts, and management of these patients is based on attenuating the procoagulant state. However, in many cases, there is no evidence of decidual thrombosis or placental vasculopathy, and instead, inflammatory signs are present (2)(3)(4). Treatment with low-dose aspirin (LDA) and heparinoids has become a conventional option for pregnant women with APS.…”
Section: Introductionmentioning
confidence: 99%
“…3 The pathogenetic role of aPL has been well established in various animal models of thrombosis and pregnancy. 1,4,5 Furthermore, several potentially procoagulant properties of aPLs have been described in cell culture models, the most prominent being their ability to induce inappropriate expression of tissue factor in monocytes and endothelial cells. 6 However, the underlying signal transduction is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%